2016
DOI: 10.1007/s00284-016-1008-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Bioleaching of Sulfur, Iron, and Silicon Impurities from Coal by Fusarium oxysporum FE and Exophiala spinifera FM with Growing and Resting Cells

Abstract: Coal is the most abundant fossil fuel containing sulfur and other elements which promote environmental pollution after burning. Also the silicon impurities make the transportation of coal expensive. In this research, two isolated fungi from oil contaminated soil with accessory number KF554100 (Fusarium oxysporum FE) and KC925672 (Exophiala spinifera FM) were used for heterotrophic biological leaching of coal. The leaching were detected by FTIR, CHNS, XRF analyzer and compared with iron and sulfate released in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In the current study, mine tailing samples, representing an extreme environment, were used to isolate fungi and eight different genera identified. These genera have been reported or linked to bioleaching activities [41,[48][49][50][51][52]. Thus, this study confirmed the importance of isolating potential bioleaching organisms from extreme environments.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, mine tailing samples, representing an extreme environment, were used to isolate fungi and eight different genera identified. These genera have been reported or linked to bioleaching activities [41,[48][49][50][51][52]. Thus, this study confirmed the importance of isolating potential bioleaching organisms from extreme environments.…”
Section: Discussionsupporting
confidence: 82%
“…The dominant fungal species in ironware and axe water samples have a certain heavy metal (Rasool and Irum 2014a, b;Rasool and Irum 2014a, b) and high salt tolerance (Grishkan and Nevo 2003). Fusarium can metabolize sulfur and iron (Etemadzadeh et al 2016), and Penicillium often colonizes cultural relics . At present, research on the biodeterioration of cultural relics is mostly focused on wooden cultural relics Liu et al 2017), mural cultural relics (Ma et al 2020;Suphaphimol et al 2022), and stone cultural relics , with few studies on metal cultural relics.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic sulfur, mostly in the forms of pyrite and sulfates, can be removed by physical desulfurization approach, such as froth flotation and gravity separation. Sulfates are barite, gypsum, and anhydrite, 4,5 while organic sulfur exists in the form of thiophene heterocyclic compounds, mercaptan, thioether, and so forth. It is mainly embedded in the macromolecular structure of coals, which is more difficult to be removed by using the conventional physical desulfurization method 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Mishra et al 11 utilized sequential leaching resulted in 50%–53% of sulfur removal from the Meghalaya coal. Using a newly isolated heterotrophic bacterial strain Fusarium oxysporum FE, Etemadzadeh et al 4 removed 34.21% of sulfur from high‐sulfur coal collected from the Zobahan Factory in Isfahan. Also, Liu et al 12 investigated the bioleaching of Yihai coals and obtained a maximum total sulfur removal of 47% by using a fungal strain, Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%